From the Fjords to the Nile - Steiner, Pål (Archaeopress, 2018)
From the Fjords to the Nile' brings together essays by students and colleagues of Richard Holton Pierce (b. 1935), presented on the occasion of his 80th birthday. Topics focus on Egypt, the Near East and the wider ancient world.